2005
DOI: 10.1111/j.1365-2966.2005.09047.x
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared imaging of 222 nearby H -strong galaxies from the Sloan Digital Sky Survey

Abstract: We present UFTI K‐band imaging observations of 222 galaxies that are selected from the Sloan Digital Sky Survey to have unusually strong Hδ absorption equivalent widths, W○(Hδ) > 4 Å. Using gim2d, the images are fitted with two‐dimensional surface‐brightness models consisting of a simple disc and bulge component to derive the fraction of luminosity in the bulge B/T. We find that the galaxies with weak or absent Hα or [O ii]λ3727 emission (known as k+a galaxies) are predominantly bulge‐dominated (with a mode of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
86
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 50 publications
(109 reference statements)
15
86
0
Order By: Relevance
“…Therefore, the precursors of post-starbursts are unlikely to grow in mass via multiple mergers in the time it takes them to quench. The burst fraction (amount of new stars formed) in a merger is typically <20% of the total mass (Norton et al 2001;Balogh et al 2005;Kaviraj et al 2007;Wild et al 2009;Swinbank et al 2012). Hence, it also does not significantly contribute to the mass increase on the starburst sequence.…”
Section: Finding a More Complete Sample Of Post-starburstsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the precursors of post-starbursts are unlikely to grow in mass via multiple mergers in the time it takes them to quench. The burst fraction (amount of new stars formed) in a merger is typically <20% of the total mass (Norton et al 2001;Balogh et al 2005;Kaviraj et al 2007;Wild et al 2009;Swinbank et al 2012). Hence, it also does not significantly contribute to the mass increase on the starburst sequence.…”
Section: Finding a More Complete Sample Of Post-starburstsmentioning
confidence: 99%
“…As such, they display both early-type morphologies and signs of interactions (Schweizer 1982;Zabludoff et al 1996;Quintero et al 2004;Balogh et al 2005;Yang et al 2008;Pracy et al 2009). Similarly, many post-starburst galaxies are observed to be blue-centered with positive color gradients and have central (within ∼4 kpc) A-star populations (e.g., Yamauchi & Goto 2005;Goto et al 2008;Yang et al 2008;Swinbank et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, post-starburst galaxies are found to be mostly bulge-dominated and/or have a morphology that is consistent with being early-type (Goto & SDSS collaboration 2003;Quintero et al 2004;Tran et al 2004;Blake et al 2004;Goto 2005;Balogh et al 2005;Poggianti et al 2009), and in some others have a high incidence of disks and spiral arms (e.g., Franx 1993;Couch et al 1994;Dressler et al 1994;Caldwell & Rose 1997;Dressler et al 1999). For example, Quintero et al (2004) visually inspected a sample of 160 galaxies from the SDSS at 0.05 < z < 0.20, and classified 90% of them as bulge-dominated systems.…”
Section: Morphologies and Structural Parametersmentioning
confidence: 99%
“…Any method using Hα is preferable in this respect. Second, they use full spectral fits rather than Balmer line equivalent widths (e.g., Balogh et al 2005). This selection alters slightly the "purity" of the sample, as any sufficiently blue continuum will lead to a K+A classification, regardless of A star content.…”
Section: Interactions Mergers Starbursts and Post-starburstsmentioning
confidence: 99%